2016
DOI: 10.1371/journal.pone.0153175
|View full text |Cite
|
Sign up to set email alerts
|

Riboflavin-Induced Disease Resistance Requires the Mitogen-Activated Protein Kinases 3 and 6 in Arabidopsis thaliana

Abstract: As a resistance elicitor, riboflavin (vitamin B2) protects plants against a wide range of pathogens. At molecular biological levels, it is important to elucidate the signaling pathways underlying the disease resistance induced by riboflavin. Here, riboflavin was tested to induce resistance against virulent Pseudomonas syringae pv. Tomato DC3000 (Pst DC3000) in Arabidopsis. Results showed that riboflavin induced disease resistance based on MAPK-dependent priming for the expression of PR1 gene. Riboflavin induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 65 publications
2
10
0
Order By: Relevance
“…In contrast, the induction of pathogen resistance by naringenin was not shown in mpk3 and mpk6 ( Figure 7 ). This observation is similar to a previous report that BTH, riboflavin and pipecolic acid induce pathogen resistance by increasing the activity of MPK3 and MPK6 ( Nie and Xu, 2016 ; Wang et al, 2018 ). These results suggest that naringenin also induces pathogen resistance through the activation of MAPK pathways.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In contrast, the induction of pathogen resistance by naringenin was not shown in mpk3 and mpk6 ( Figure 7 ). This observation is similar to a previous report that BTH, riboflavin and pipecolic acid induce pathogen resistance by increasing the activity of MPK3 and MPK6 ( Nie and Xu, 2016 ; Wang et al, 2018 ). These results suggest that naringenin also induces pathogen resistance through the activation of MAPK pathways.…”
Section: Discussionsupporting
confidence: 92%
“…SA-mediated immune responses are reported to be activated by the coordination of different NPR proteins ( Backer et al, 2019 ). It has been reported that pathogen resistance inducing molecules confer pathogen resistance in NPR1 dependent manner ( Nie and Xu, 2016 ; Yang et al, 2016 ). In this study, we showed that naringenin not only increased SA level by induction of SA biosynthetic gene ( Figures 3 , 4 ) but also induced nuclear translocation of NPR1 ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a plant pathogen, Agrobacterium triggers plant immunity characterized by MPK3/MKK6 activation, and defense-responsive gene induction ( Figure 1 ). This process is similar to the responses to other plant pathogens such as Pst DC3000 (Nie and Xu, 2016 ).…”
Section: Discussionsupporting
confidence: 57%
“…Several members of the MAPK family have been shown to be directly activated by the ABA signaling pathway (de Zelicourt et al ). The activation of MPKs was proved to be responsible for the enhanced expression of defense related genes and the subsequent enhanced stress resistance (Beckers et al , Nie and Xu , Mauch‐Mani et al ). In the present study, drought priming led to an upregulation of both FaMPK3 and FaMPK6 ; however, FaMPK6 was not affected by ABA (Fig.…”
Section: Discussionmentioning
confidence: 99%